Faith, relief and development: the UMCOR-Muslim Aid model seven years on - Saleem, A; Hovey, G (Refugee Studies Centre, University of Oxford, 2014)
Seven years ago, a strategic partnership between the United Methodist Committee on Relief and Muslim Aid in Sri Lanka was formalised into a worldwide partnership agreement. The partnership offered a model for community-based, culturally appropriate and sustainable assistance provision – so why did the partnership not reach these goals?